When a bad day at the golf course is a bad day at the office: occupational stressors, institutional supports, and the mental health of NCAA golf coaches - Laura Upenieks; Brendan M. Ryan; Howie J. Carson (Frontiers Media S.A., 2023)
This study examined the mental health of NCAA collegiate golf coaches. Utilizing the person-environment fit theory and previous literature on coaches' well-being, this study examined four outcomes among 48 participants, namely: depressive and anxiety symptoms, burnout, and job turnover intentions. Results suggested that coaching stressors (e.g., administrative tasks, practice plans, pressure to win) only associate with greater burnout. More consistent evidence showed that workplace stress (e.g., lack of control and autonomy, poor work-family balance) associated with higher levels of all outcomes. Finally, greater perceived organizational support had a beneficial association with each outcome. The findings of the current study suggest golf coaches are at risk of mental health problems because of the stressors of this job. Taken as a whole, athletic departments, coaches, and student-athletes must reconsider norms that overemphasize performance and underemphasize self-care and work-life balance.